FROM STORYTELLING TO STORY WRITING: THE IMPLEMENTATION OF READING TO LEARN (R2L) PEDAGOGY TO TEACH ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Damayanti, Ika Lestari (Indonesian Journal of Applied Linguistics, 2017)
It is widely acknowledged that the use of stories supports the development of literacy in the context of learning English as a first language. However, it seems that there are a few studies investigating this issue in the context of teaching and learning English as a foreign language.  This action-oriented case study aims to enhance students’ written narrative achievement through a pedagogical intervention that incorporates oral story sharing activities. In this paper, the intervention will be briefly described and the preliminary findings from the students’ written texts will be presented. This study which was conducted in a lower secondary school in Bandung Barat region, Indonesia implemented the intervention within eight learning periods. The intervention comprised the following stages: (1) preparing before reading (stories), (2) detailed reading, (3) joint rewriting, and (4) individual rewriting. Before and after the intervention, students’ narrative texts were collected and analysed in terms of how each text achieved its purpose, how it moved through stages and phases of meaning, the control of field, relationship with the reader and its coherence.  The preliminary findings indicate that there is a shift in students’ ability from writing fragmented and spoken-like language to more literate written narratives.   It is expected that this study which implemented R2L pedagogy in the Indonesian context will contribute to English language teaching in EFL contexts.